Operating Cash Flows, Foreign Ownership, and Solvency on Tax Avoidance - Nahda Paramitha; Kurnia Kurnia (Jurnal Akuntansi, 2023)
The government uses tax collection as a strategy to increase national income, but companies are trying to reduce the amount of tax that must be removed. This is what causes the practice of tax avoidance. The focus of this research is how factors such as operating cash flow, foreign ownership, and solvency affect tax avoidance. This study applied a purposive sampling technique for the sample, with a total of 18 companies selected as research objects from 2017 to 2021 and obtained 87 observational data from companies in the mining industry sector listed on the IDX. The data is examined using a technique called panel data regression analysis using Eviews 12 in its processing. The results reveal that operating cash flow, foreign ownership, and solvency affect simultaneously. However, partially operating cash flow has an effect on tax avoidance and for foreign ownership and solvency does not partially affect tax avoidance. Keywords: Tax Avoidance, Operating Cash Flow, and Foreign Ownership, Solvency